Effect of Rare Earth Elements Addition and Sintering Conditions on the Microstructure and Microhardness of Inconel 718 - Medrano-Prieto, H. M.; Santos-Beltrán, A.; Gallegos-Orozco, V.; Santos-Beltrán, M. M.; Camacho-Montes, H.; Garay-Reyes, C. G.; Ruiz-Esparza-Rodriguez, M. A.; Estrada-Guel, I.; Rodríguez-Cabriales, G.; Guía-Tello, J. C.; Mendoza-Duarte, J. M.; Silva-Aceves, J. M.; et al. (Metallography, microstructure, and analysis, 2024)
A series of Inconel 718 alloys modified by additions of 0.1-0.3 of a mixture of rare earth elements Ce:La:Nd:Pr have been synthesized by powder metallurgy. These alloys were sintered by conventional and hot isostatic pressure methods and subject to standard aging treatment. The results showed that adding rare earth elements generates γ′ and γ″ precipitates with a minor size than those reported. Additionally, the presence of rare earth elements causes the formation of La-Ti-Al-O phases that act as reinforcing particles. The highest microhardness values were obtained in the samples with 0.3 wt.% of rare earth elements and sintered by hot isostatic pressure. These hardness values are attributed to the precipitation of the nanophases (γ′ and γ″), the high numeric density of dispersed oxides and carbides, and solid solution strengthening generated by rare earth elements addition and dissolution of elements in the Nb, Ti and Mo rich phases.